An empirical exploration of information security management system (ISMS) in Malaysian Public Sector: A PLS-SEM method - Ibrahim N.; Ali N. (Mattingley Publishing, 2023)
Industrial management; Least squares approximations; Regulatory compliance; Scanning electron microscopy; Security of data; Security systems; Information security management systems; ISMS; Organizational factors; Public sector; Success factors; Information management